2017
DOI: 10.1105/tpc.16.00975
|View full text |Cite
|
Sign up to set email alerts
|

Repression of miR156 by miR159 Regulates the Timing of the Juvenile-to-Adult Transition in Arabidopsis

Abstract: Temporally regulated microRNAs have been identified as master regulators of developmental timing in both animals and plants. In plants, vegetative development is regulated by a temporal decrease in miR156 level, but how this decreased expression is initiated and then maintained during shoot development remains elusive. Here, we show that miR159 is required for the correct timing of vegetative development in Loss of miR159 increases miR156 level throughout shoot development and delays vegetative development, wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
137
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
3
2
2

Relationship

2
8

Authors

Journals

citations
Cited by 160 publications
(142 citation statements)
references
References 38 publications
4
137
0
1
Order By: Relevance
“…These results indicate that amp1 has no effect on the activity of miR156, implying that translational repression of SPL9 occurs normally in amp1 . To determine if miR156 is uniquely insensitive to amp1 , we examined the effect of amp1 on the expression of MYB33, a transcription factor that also regulates shoot identity (Guo et al, 2017) and is translationally repressed by miR159 (Li et al, 2014). miR159-sensitive and miR159-resistant versions of MYB33-GUS (Millar and Gubler, 2005) were crossed into amp1 , and WT and amp1 plants were stained for GUS activity one week after germination, and at flowering.…”
Section: Resultsmentioning
confidence: 99%
“…These results indicate that amp1 has no effect on the activity of miR156, implying that translational repression of SPL9 occurs normally in amp1 . To determine if miR156 is uniquely insensitive to amp1 , we examined the effect of amp1 on the expression of MYB33, a transcription factor that also regulates shoot identity (Guo et al, 2017) and is translationally repressed by miR159 (Li et al, 2014). miR159-sensitive and miR159-resistant versions of MYB33-GUS (Millar and Gubler, 2005) were crossed into amp1 , and WT and amp1 plants were stained for GUS activity one week after germination, and at flowering.…”
Section: Resultsmentioning
confidence: 99%
“…Pollen miRNA target mRNAs are involved both in pollen grain development and pollen tube germination and include well-known regulators of these processes such as SK32, AtbZIP34 and AFB3 involved in pollen development 41-43 , or MYB97, MYB101 , and SYP131 involved in pollen tube germination 44,45 . miRNAs with a higher number of targeted transcripts included juvenile-to-adult phase transition related miR172 46 and miR159 47 (13.5 and 10% of targeted genes) and also the pollen specific miR5021 (10% of targeted genes) (Figure 4b). miRNA targets included classic miRNA-regulated genes, such as the TAS genes or miR172-targeted transcription factors APETALA2 (AP2) and TARGET OF EARLY ACTIVATION TAGGED (EAT) 2 (TOE2) (Supplementary Figure 4).…”
Section: Resultsmentioning
confidence: 99%
“…Hence, the dual LUC assays revealed very significant silencing of the firefly LUC reporter when ath-MIR159 and the predicted target sequence of the MYB33 domain protein were co-agroinfiltrated, indicating that genomic stress ‘shock’ may act throughout miR159/MYB33 module under xenobiotic induced stress. Guo et al . (2017) showed that the loss of miR159 resulted in miR156 increased level.…”
Section: Discussionmentioning
confidence: 99%